1999
DOI: 10.1159/000024956
|View full text |Cite
|
Sign up to set email alerts
|

Sequence Analysis of the Matrix/Nucleocapsid Gene Region of Turkey Coronavirus

Abstract: A reverse transcriptase, polymerase chain reaction (RT-PCR) procedure was used to amplify a segment of the genome of turkey coronavirus (TCV) spanning portions of the matrix and nucleocapsid (MN) protein genes (approximately 1.1 kb). The MN gene region of three epidemiologically distinct TCV strains (Minnesota, NC95, Indiana) was amplified, cloned into pUC19, and sequenced. TCV MN gene sequences were compared with published sequences of other avian and mammalian coronaviruses. A high degree of similarity (>90%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…RT-PCR protocols have been commonly and successfully applied in the USA and the UK (Breslin et al ., 1999a(Breslin et al ., ,b, 2000. We have used RT-PCRs, histopathological and immunohistochemical examination, and have compared them for detection of TCoV.…”
Section: Discussionmentioning
confidence: 99%
“…RT-PCR protocols have been commonly and successfully applied in the USA and the UK (Breslin et al ., 1999a(Breslin et al ., ,b, 2000. We have used RT-PCRs, histopathological and immunohistochemical examination, and have compared them for detection of TCoV.…”
Section: Discussionmentioning
confidence: 99%
“…Sequence analysis of these clones revealed that both newly isolated avian coronaviruses had the S-3-M-5-N gene order that is typical of group 3 coronaviruses from chicken (IBV) (Boursnell et al, 1987), turkey (Breslin et al, 1999a;Cavanagh et al, 2001;Lin et al, 2002) and pheasant (Cavanagh et al, 2002).…”
Section: Partial Genome Organization Of the Two Coronavirus Strainsmentioning
confidence: 99%
“…The number of such genes varies among coronaviruses, including among species within a given group (reviewed by Enjuanes et al ., 2000;Cavanagh, 2005). In the case of IBV, TCoV and PhCoV there are two such genes, numbers 3 and 5 (Boursnell et al ., 1987;Breslin et al ., 1999a;Cavanagh et al ., 2001Cavanagh et al ., , 2002. Each of these genes encodes two non-structural proteins: 3a and 3b, 5a and 5b ( Figure 2).…”
Section: Structural Features Of Coronavirusesmentioning
confidence: 99%